DIET OF GIRARDINICHTHYS MULTIRADIATUS (MEEK, 1904) (PISCES: GOODEIDAE) IN THE CIENEGA OF CHIGNAHUAPAN, MEXICO - Cruz-Gómez, Adolfo (2021)
The diet of Girardinichthys multiradiatus (Meek, 1904) in the swamp of Chignahuapan, State of Mexico, was analyzed. The organisms were collected in 2012 covering the climatic dry and rainy seasons. For the analysis of stomach contents, 602 organisms (336 females and 266 males) with sizes between 1.0 and 4.6 cm were studied. The results showed a consumption of 13 food types, of which cladocerans and copepods were the most consumed in both seasons. Similar data showed ontogenic factors. The niche amplitude, according to the Levins index, was low for both sexes due to the high consumption of cladocerans, while the Zander Main Food Index, showed cladocerans and diptera as essential prey in their diet. These data change slightly by climatic season, since it depends on the environmental characteristics of the system, as well as the composition and abundance of the resources consumed by this species. In this sense, and according to Zander, only male's copepods were essential prey during rains, while. Female, hemipterans and diptera were main prey during dry season. In general, these results contribute to the knowledge of the food ecology of this species in the State of Mexico, and being endemic, it is necessary to know more about its biology and ecology to establish strategies that contribute to its conservation.